Randomized controlled trial: Role of glycerin suppository for promoting feeding tolerance in preterm very low birth weight neonates - Sharma, Abhinav; Bansal, Rajesh; Bhambri, Alka; Chaudhary, Sanjata Roy (Indian Journal of Child Health, 2022)
Background: Feeding intolerance is a common problem in preterm infants delaying establishment of full enteral feeding (FEF). Sustained parenteral nutrition has many disadvantages. To promote feeding tolerance, glycerin suppository is being used. Aims: (a) To compare the efficacy of glycerin suppository versus no intervention in preterm, very low birth weight (VLBW) neonates in achieving FEFs, i.e., 180 ml/kg/day for at least 24 hrs both the groups. (b) Correlation of glycerin suppository with time to regain birth weight, necrotizing enterocolitis, and adverse effects following glycerin suppository. Materials and Methods: The present study is a prospective randomized control trial; study population - 50 VLBW (birth weight between 1000 and 1500 g) or preterm (gestational age between 28 and 32 weeks) neonates randomized to either glycerin suppository group or non-intervention group. Intervention group – glycerin suppository (1 g) once daily from day 2 to day 14 of life or non-intervention along with intermittent oral feeds and standardized care. Results: A total of 58 neonates were assessed for eligibility, 50 randomized to either glycerin suppository group or control group, 19 neonates in both the groups were analyzed for outcome. Mean time to achieve FEFs was 11.57±1.21 days in glycerin suppository group and 11.84±1.25 days in control group which was not statistically significant (p=0.441; RR=0.67; 95% confidence interval=?0.539, 1.079). There was no significant difference observed in secondary outcomes. Conclusion: Prophylactic glycerin suppositories did not reduce the time to achieve FEFs in preterm VLBW neonates in our setting.